Using the TEI Writing System Declaration (WSD). - Birnbaum, David J.; Cournane, Mavis (Computers & the Humanities, 1999)
Relates how authors of language transcripts have used the Text Encoding Initiative (TEI) Writing System Declaration (WSD) to support the transformation of TEI-conformant documents. Function of the WSD mechanism; Implementations with different approaches for encoding and rendering in WSD; Use of a character entity from the Cyrillic SGML SDATA entry entity set; Emphasis on the need for dynamic WSD processing.